Strengthening Justice and Accountability: The Role of Ombudsman in Monitoring Police Public Services - Oktobrian, Dwiki; Natasya, Juliana Dwi; Wiranti , Cece; Sudrajat, Tedi (Universitas Kuningan, 2025)
Public service delivery in police sector of Indonesia is facing a crisis of trust, fueled by widespread reports of maladministration. In this context, social movements such as #PercumaLaporPolisi (Reporting to Police Is Useless) and incidents of police brutality have reinforced perceptions that law enforcement lacks transparency, responsiveness, and accountability. Therefore, this research aims to 1) identify the forms and patterns of maladministration in police public services, and 2) evaluate the role and effectiveness of Indonesian Ombudsman, with a specific focus on West Java Regional Office, to address and prevent maladministration. Document analysis, literature review, and interviews were integrated with key informants using a socio-legal and qualitative method. The results showed that the most frequently reported problems included investigation and prosecution procedures, such as Notice of Investigation Progress, Notice of Investigation Commencement, and Notice of Investigation Completion, as well as initial complaint handling. The issues were largely driven by rigid bureaucracy, resistance to external monitoring, and limited enforcement of Ombudsman recommendations. However, the illegally bound recommendations supported procedural reform. This was evident in the achievement of green zone status for compliance with service standards across all district police offices in West Java by 2024. The objectives of Goal 16 (Sustainable Development Goals/SDGs) were also supported to promote peace, justice, and strong institutions by emphasizing the importance of independent oversight in building accountable and humane police institutions based on public trust.